Portuguese Architecture in Transit(ion) - Bruno Gil; Susana Lobo; José Ribau Esteves (Footprint)
In the final years of the Estado Novo regime (1933–1974), the Amsterdam Town Hall International Competition of 1967 presents the opportunity for seven teams of Portuguese architects to confront their own reality and rehearse distinct visions of building and city. From a national context, politically and geographically distant from the heart of the disciplinary debate of the 1960s, the proposals submitted set the terms on which Portugal competes in Amsterdam, revealing in the diversity of approaches and experiences forwarded by this new generation of architects the vitality of Portuguese architecture on its path to internationalisation.